Total colonic aganglionosis: multicentre study of surgical treatment and patient‐reported outcomes up to adulthood. Issue 5 (13th July 2020) - Stenström, P.; Kyrklund, K.; Bräutigam, M.; Engstrand Lilja, H.; Juul Stensrud, K.; Löf Granström, A.; Qvist, N.; Söndergaard Johansson, L.; Arnbjörnsson, E.; Borg, H.; Wester, T.; Björnland, K.; et al.
Abstract : Background: Surgery for total colonic aganglionosis (TCA) is designed to preserve continence and achieve satisfactory quality of life. This study evaluated a comprehensive group of clinical and social outcomes. Methods: An international multicentre study from eight Nordic hospitals involving examination of case records and a patient‐reported questionnaire survey of all patients born with TCA between 1987 and 2006 was undertaken. Results: Of a total of 116 patients, five (4·3 per cent) had died and 102 were traced. Over a median follow‐up of 12 (range 0·3–33) years, bowel continuity was established in 75 (73·5 per cent) at a median age of 11 (0·5–156) months. Mucosectomy with a short muscular cuff and straight ileoanal anastomosis (SIAA) (29 patients) or with a J pouch (JIAA) (26) were the most common reconstructions (55 of 72, 76 per cent). Major early postoperative complications requiring surgical intervention were observed in four (6 per cent) of the 72 patients. In 57 children aged over 4 years, long‐term functional bowel symptoms after reconstruction included difficulties in holding back defaecation in 22 (39 per cent), more than one faecal accident per week in nine (16 per cent), increased frequency of defaecation in 51 (89 per cent), and social restrictions due to bowel symptoms in 35 (61 per cent). Enterocolitis occurred in 35 (47 per cent) of 72 patients. Supplementary enteral and/or parenteral nutrition was required by 51 (55 per cent) of 93 patients at any time during follow‐up. Of 56 responders aged 2–20 years, true low BMI for age was found in 20 (36 per cent) and 13 (23 per cent) were short for age. Conclusion: Reconstruction for TCA was associated with persistent bowel symptoms, and enterocolitis remained common. Multidisciplinary follow‐up, including continuity of care in adulthood, might improve care standards in patients with TCA. Abstract : In a multicentre study, outcome of surgery for total colonic aganglionosis was evaluated in 116 patients. In long‐term follow‐up, patients with a J pouch reconstruction reported better faecal continence and those with a Duhamel reconstruction reported fewer episodes of enterocolitis. Nutritional support was needed extensively in all groups with various lengths of resected aganglionotic bowel. Problems persist into adulthood Abstract : Antecedentes: La cirugía de la aganglionosis colónica total ( total colonic aganglionosis, TCA) está diseñada para preservar la continencia y lograr una calidad de vida satisfactoria. Este estudio evaluó un gran número de resultados clínicos y sociales. Métodos: Se realizó un estudio internacional multicéntrico en ocho hospitales nórdicos en el que se incluyeron las historias clínicas de todos los pacientes nacidos con TCA entre 1987 y 2006. Se invitó a los pacientes y a sus cuidadores a responder una encuesta sobre la función intestinal, el crecimiento y las necesidades nutricionales, así como la repercusión social de la enfermedad a largo plazo. Resultados: De un total de 116 pacientes, 5 (4, 3%) habían fallecido y 102 respondieron la encuesta. Con una mediana de seguimiento de 12 años (rango 0, 5–33), se había restablecido la continuidad intestinal en 75/102 (74%) a una mediana de edad de 11 meses (0, 5‐156). La mucosectomía con un manguito muscular corto y anastomosis ileoanal directa ( short muscular cuff and straight ileo‐anal anastomosis, SIAA) n = 29 o con reservorio en J (JIAA) n = 26 (55/72, 76%) fueron las reconstrucciones más habituales. Las complicaciones postoperatorias precoces que precisaron una intervención quirúrgica fueron muy poco frecuentes, pero se presentaron en 4/72 (5%) pacientes. Los síntomas a largo plazo relacionados con la función intestinal tras la reconstrucción, valorados en 57 niños mayores de cuatro años, fueron la dificultad para retener la defecación en 14 (25%), la encopresis en 21 (37%), las pérdidas fecales > 1/semana en 9 (16%) y el aumento de la frecuencia de defecación en 51 (89%). A largo plazo, se desarrolló una enterocolitis en 35/72 (47%) pacientes. Se precisó de nutrición enteral y/o parenteral suplementaria en algún momento del período de seguimiento en 51/93 (55%) pacientes. En los pacientes que respondieron a la encuesta entre 2 y 20 años ( n = 56) de edad, se detectó un índice de masa corporal menor en 20 (35%) y una altura baja en 13 (23%) para su edad. En 35/57 (61%) pacientes mayores de 4 años con restauración del tránsito intestinal había restricciones sociales debido a los síntomas intestinales, de los que en 10 (17%) casos fueron moderadas o graves. Conclusión: La reconstrucción de una TCA se asocia con síntomas intestinales persistentes y la enterocolitis sigue siendo frecuente. Un seguimiento multidisciplinario, incluso en la edad adulta, podría mejorar los resultados en la cirugía de la TCA.